The Adaptation and Validation of Adolescent Emotional Competence Scale for Indonesian Adolescents - Desiningrum, Dinie Ratri; Arywibowo, Jessica Dhoria (HUMANITAS published by Universitas Ahmad Dahlan., 2024)
Assessing emotional competence is crucial for understanding how adolescents handle negative emotions and form their future scenarios. However, none of the Emotional Competency measurements are available for Indonesian’ adolescents. This research aimed to adapt and validate the short version of the Emotional Competency Scale for Indonesian adolescents. 352 high school students were selected as participants through a cluster sampling method. Twenty indicators of the Short Version of the Emotional Competence Scale were employed to collect data. The data was analysed using Second Order Confirmatory Factor Analysis (CFA) in the Lisrel 7.9 program to determine the scale's reliability and validity. The results showed that 18 indicators had loading factors larger than 0.5; the CR and AVE values were greater than 0.7 and 0.5, respectively. Thus, the 18 indicators of the Short Version of the Emotional Competency Scale demonstrated validity and reliability and were suitable for widespread use among Indonesian adolescents.